Our lives depend on them - Qamaruz Zaman, Faridah (University Putra Malaysia, 2012)
It is easy to take for granted the functions that FRUITS serve us and animals. Try to imagine a life without your favourite breakfast of nasi lemak (coconut rice) if you are a Malaysian, cereals and bread if you are from United Kingdom or United States of America. What rice, cereals and bread have in common is that they all are fruits from the Grass family (Poaceae). Thousands of years of careful selection, breeding and cultivation have created the optimal varieties for human needs; from nutritional content, to desirable looks and ease of harvest by mechanization. The artifact Grassy Starch will astound the viewers with an appreciation of the inherently simple yet spiritual beauty from the humble cereals.